2022
DOI: 10.1002/hyp.14469
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of National Water Model retrospective analysis snow outputs at snow telemetry sites across the Western United States

Abstract: This study compares the US National Water Model (NWM) reanalysis snow outputs to observed snow water equivalent (SWE) and snow-covered area fraction (SCAF) at snow telemetry (SNOTEL) sites across the Western United States. SWE was obtained from SNOTEL sites, while SCAF was obtained from moderate resolution imaging spectroradiometer (MODIS) observations at a nominal 500 m grid scale. Retrospective NWM results were at a 1000 m grid scale. We compared results for SNOTEL sites to gridded NWM and MODIS outputs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…We note that while Noah-MP's simulation of fSCA was too high relative to observed fSCA, as also noted in other studies [20,50], more realistically simulating fSCA might degrade the simulation of SWE since the surface albedo, rather than the snow albedo, is used to calculate the energy balance at the snow's surface. Per Noah-MP's parameterization: Surface Albedo = Soil Albedo (1 − fSCA) + Snow Albedo (fSCA) (10) where Snow Albedo = ƒ f(snow age, zenith angle) Noah-MP's energy budget calculation would be more accurate if Noah-MP calculated an energy balance for snow-covered and non-snow-covered surfaces separately and then averaged the resulting fluxes of energy and mass within the grid cell, rather than its current method of using a grid cell average albedo (Equation ( 9)).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…We note that while Noah-MP's simulation of fSCA was too high relative to observed fSCA, as also noted in other studies [20,50], more realistically simulating fSCA might degrade the simulation of SWE since the surface albedo, rather than the snow albedo, is used to calculate the energy balance at the snow's surface. Per Noah-MP's parameterization: Surface Albedo = Soil Albedo (1 − fSCA) + Snow Albedo (fSCA) (10) where Snow Albedo = ƒ f(snow age, zenith angle) Noah-MP's energy budget calculation would be more accurate if Noah-MP calculated an energy balance for snow-covered and non-snow-covered surfaces separately and then averaged the resulting fluxes of energy and mass within the grid cell, rather than its current method of using a grid cell average albedo (Equation ( 9)).…”
Section: Discussionmentioning
confidence: 62%
“…Although the precipitation bias was not the dominant factor contributing to the differences in SWE and SD in this study, the biases, if present along with the biases of T2m, would have a major impact on snow versus rain and thus in the simulated SWE and SD. A study of NWM reanalysis snow outputs for observed SWE in the western US showed that the errors in precipitation inputs were more important than the cooler temperature bias, as the NWM generally underpredicted the SWE [20]. This shows that the contribution of inputs in the NWM simulation might have regional differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommended next steps are to understand individual dust layer dynamics [68] in relation to sub-seasonal snow and climate variables, to incorporate weather forecasts into snowpack energy balance modeling [94] and develop a real-time dust-enhanced energy absorption forecast product for operational end-users. Operational streamflow forecasting is challenging [95], and snowpack and hydrological models are often too complex to be very useful in a forecast setting [96,97]. A hierarchal decision tree approach [98] could be constructed to prioritize most important variables as the snow season unfolds.…”
Section: Implications and Uses Of This Workmentioning
confidence: 99%